B-cell chronic lymphocytic leukaemia in an African lion (Panthera leo) - R. Meoli; C. Eleni; P. Cavicchio; M.C. Tonnicchia; B. Biancani; L. Galosi; G. Rossi (Veterinární Medicína, 2018)
A 15-year-old female African lion (Panthera leo) maintained at the Zoological Garden of Pistoia, Tuscany (Italy), showed signs of malaise, dyspnoea, tremors, pale mucous membranes and ataxia for two days prior to death. Complete blood count showed anaemia, thrombocytopaenia and severe lymphocytosis. At autopsy, the most relevant finding was severe, generalised splenomegaly. Histologically, high numbers of neoplastic lymphocytes diffusely infiltrated the spleen, liver, heart, pancreas, kidney and lungs. The lymphoid cells were positive for CD79a and negative for CD3 on immunohistochemistry. The histologic features of the neoplastic cells and their immunophenotype are consistent with B-cell lymphocytes. Based on surface membrane co-expression of immunoglobulin M and immunoglobulin D in most neoplastic cells, which indicated that they were naïve, antigen-inexperienced and mature circulating resting B-cells, and consistent with their appearance as small lymphocytes with high nuclear-to-cytoplasmic ratios, a diagnosis of B-cell chronic lymphocytic leukaemia was made.